Use of a paediatric advice line for parents of infants recruited to a randomised controlled trial - Nigel Curtis; Joyce Chan; Laure F Pittet; Veronica Abruzzo; Lianne Cox; Clare Morrison; Vanessa Clifford; Samantha Bannister; Clare Brophy; Hannah Elborough; Kate Wall; Jordan Kirby; et al. (BMJ Publishing Group, 2023)
Background This study aims to describe the use of a paediatric advice line (PAL) provided to parents whose infants were recruited to a large randomised controlled trial (RCT), including the number and types of medical concerns addressed, seasonal variability and call outcomes. Additionally, sociodemographic characteristics of the parents and children of those parents who used the PAL are compared with those who did not.Methods Prospective cohort of 1246 children nested in the Melbourne Infant Study: BCG for Allergy and Infection Reduction (MIS BAIR) RCT. All MIS BAIR participants were offered access to the PAL. Data were collected over the initial 2 years of a 5-year follow-up. Data were analysed using χ2 tests, and ORs were calculated using multiple logistic regression.Results The PAL was used by 230 (18.5%) participants, who made a total of 586 calls during the 2-year study period. The reasons for calling the PAL were dermatological (24%); gastrointestinal (18%); disturbances in feeding, sleeping and crying (14%); respiratory (7%); and developmental/neurological (6%). Analysis revealed that those who used the PAL were more likely to be first-time parents (OR 1.4, 95% CI 1.1 to 1.9) and mothers who hold a university degree (OR 3.3, 95% CI 1.3 to 8.4). PAL costs were minimal and comprised 15 clinicians with paediatric experience.Conclusions A cost-effective PAL service for clinical trial participants was used appropriately by parents for relatively minor concerns and may have a role in trials to promote participant engagement and reduce demand for other health services.